Implementation of Village Zakat Index 2.0 in Supporting the Zakat Community Development Program - Syafiqah, Farras; Firdaus, Achmad; Zainal, Muhammad Hasbi (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2024)
Poverty remains a significant issue in Indonesia, and natural disasters also play a role in affecting the economic conditions of communities. Pantai Bahagia Village is the area most impacted by tidal flooding. This research was conducted to assess the material and spiritual conditions of Pantai Bahagia Village and its eligibility to receive zakat funds. This study employs a mixed-methods approach, combining qualitative and quantitative methods with the Zakat Village Index (IDZ) 2.0 (Multi-Stage Weighted Index) as the analytical tool.. The results show that the IDZ 2.0 score in Pantai Bahagia Village is 0.56, which means the village is in a fairly good condition to be considered for zakat fund support. The findings of this research can serve as a reference for zakat institutions or the government in disbursing zakat funds, designing targeted programs, monitoring progress, and increasing community participation, which ultimately can improve the welfare of the community.